Determinan Peringkat Sukuk Korporasi Pada Pasar Modal di Indonesia Tahun 2014-2020 - Agustin, Eka (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2021)
This study aims to determine and provide empirical findings whether profitability, liquidity, leverage, productivity, firm size, and age of sukuk have an influence on sukuk ratings. The sample used is companies that issue sukuk and are listed on the Indonesia Stock Exchange. The data analysis technique uses multiple linear regression analysis with the help of SPSS 23. The results of this study indicate that the firm size and age of the sukuk have an effect on the sukuk rating. Meanwhile, profitability, liquidity, leverage, and productivity have no effect on the sukuk rating.